The Improvement of Strategic Alliances Management As A Basis for Raising Agricultural Production Competitiveness in the Regional Agribusiness (International Journal of Psychosocial Rehabilitation, 2020)
The paper summarizes classical approaches to interpreting the notion of “competitiveness.” The paper also specifies the economic essence of agricultural enterprise competitiveness as a means for this enterprise to manufacture products that are in demand in the market and that have priority over other types of products. It investigates organizational and economic aspects of strategic interactive alliances and prerequisites for clustering manufacturers and processors of agricultural alliances’ products, which provides its reliability and competitiveness. It proves the necessity of using interaction marketing instruments in agriculture due to its specific features caused by a great number of agricultural commodities manufacturers and a small number of their consumers. The paper proves theoretically that the use of marketing interaction mechanisms creates prerequisites for developing strategic integrative alliances. The article shows alliances strategic potentials and advantages under economic globalization. Besides, it defines a general outline for creating strategic alliances based on agribusiness sectors.